Pateros - Nocheseda, Elmer I. (Pateros printed by R.O. Santos, 2010)
History and culture of Pateros, Philippines.
"Florid script of "Pateros" from Dr. Jose Rizal's handwriting."
Keywords: Pateros (Philippines) -- History; Pateros (Philippines) -- Social conditions; Pateros (Philippines) -- Economic conditions